WISDOM IN JOHN GRISHAM’S THE RAINMAKER - Charsen Watuseke; Elisabeth Z. Oroh; Clara C. Mamentu (JELLT (Journal of English Language and Literature Teaching), 2020)
The purpose of this study is to reveal Wisdom in Rudy Baylor as the main character of the novel and how he uses it. In conducting this research, the writers use descriptive qualitative research. The writers take the novel The Rainmaker as the primary source and supported by other relevant sources such as books, documents, and internet browsing as the secondary source. The objective approach is applied. The writers employ an objective approach as the primary source because the data are taken from the work itself and to see the interrelationship between the elements of the novel. The result shows that Rudy shows the quality to be wise since he is a teenager which means Rudy has wisdom. Rudy uses his wisdom in a way of how he interacts with his Black Family which is the client of Rudy, how he needs to behave and build a relation and compassion with his client according to the situation, and how Rudy as a new-qualify and inexperienced lawyer makes plans, tactics, and movements to defeat the big insurance company Great Benefit’s legendary attorney.